Initial assessment of a novel delivery system (NuDEL™®) for the covered Cheatham-Platinum stent. (15th June 2017) - Morgan, Gareth J.; Kenny, Damien; Duke, Christopher; Walsh, Kevin P.; Qureshi, Shakeel A.
Abstract: Aims: We sought to evaluate the first-in-man use of a new system for implantation of covered stents in patients with complex structural and CHD. Methods and results: Retrospective data were collected of the first 13 NuDEL™ delivery systems used in patients. The NuDEL™ comprises a covered Cheatham-Platinum stent mounted on a balloon-in-balloon and pre-loaded in a long delivery sheath. Data were collected from three centres in the United Kingdom and Ireland. A total of 13 covered stents were delivered via 12 NuDEL™ delivery systems in 12 patients. Among them, six patients had coarctation of the aorta, five patients had right ventricular outflow tract stenosis, and one patient had severe stenosis of a Mustard systemic venous baffle. There were no complications, and all the stents were deployed in the desired position with satisfactory haemodynamic results. Conclusions: The development of a bespoke system of a pre-mounted, pre-loaded covered stent may negate some of the technical challenges that complicate large-calibre stent deployment. Our preliminary results suggest that the NuDEL™ system is a safe and effective means of covered stent deployment in challenging anatomy.